Utility of inscyd athletic performance software to determine maximal lactate steady state and maximal oxygen uptake in cyclists - Podlogar, T.; Cirnski, S.; Bokal, Š.; Kogoj, T. (Journal of Science and Cycling, 2022)
Serious amateur and elite athletes regularly take part in structured physiological testing sessions so that their progress gets tracked and training loads in the training plan correctly prescribed. Commonly, athletes are tested for the maximal oxygen uptake (VO2max) and maximal lactate steady state intensity (MLSS). While for the former expensive laboratory equipment is required, the latter requires multiple exercise trials for accurate determination. INSCYD athletic performance software is designed to enable continuous monitoring of these two parameters throughout the season after undertaking a single visit exercise testing session involving blood lactate sampling and power output measurement. The purpose of the present study was to assess validity of the software by its estimates of VO2max and MLSS and compare them to gold standard laboratory measures. 11 trained participants (VO2max 61.0 ± 7.9 mL · kg-1 · min-1) took part in this study consisting of formal graded VO2max test, multiple MLSS trials and a recommended test to obtain the data later fed the INSCYD athletic performance software. Both VO2max relative (=0.13 ml.kg-1.min-1, p=0.885) and MLSS calculated values (Delta=2 W, p=0.655) were within expected daily variation and thus the estimations considered valid. It can be concluded that INSCYD athletic performance software offers its users utility to accurately predict VO2max and MLSS provided that the practitioner has a good idea of where the MLSS lies. However, caution is required when interpreting other parameter estimates provided by the software due their questionable scientific validity.